2019
DOI: 10.1093/hmg/ddz074
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis revealed sex-specific gene expression in asthmatics

Abstract: Global gene-expression analysis has shown remarkable difference between males and females in response to exposure to many diseases. Nevertheless, gene expression studies in asthmatics have so far focused on sex-combined analysis, ignoring inherent variabilities between the sexes, which potentially drive disparities in asthma prevalence. The objectives of this study were to identify (1) sex-specific differentially expressed genes (DEGs), (2) genes that show sex-interaction effects and (3) sex-specific pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 63 publications
3
25
1
Order By: Relevance
“…Moreover, ours is first study of sex specific responses that used personalized HLA read alignments to generate unbiased gene expression data at these highly polymorphic loci. Previous studies of sex differences in HLA gene expression 35,[47][48][49] did not account for this potential bias, and gene expression studies that did use personalized alignments of HLA genes did not examine sex differences 50,51 . Using unbiased estimates of HLA gene expression levels and genome-wide approaches to identify sex-specific patterns, we made the novel observation of an enrichment of LPS responses exhibiting sex by treatment interactions among class I and II HLA genes compared to all autosomal genes: 47% of HLA genes showed sex by treatment interactions whereas these interactions were observed in 8% of all autosomal genes (P = 1.1 × 10 -4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ours is first study of sex specific responses that used personalized HLA read alignments to generate unbiased gene expression data at these highly polymorphic loci. Previous studies of sex differences in HLA gene expression 35,[47][48][49] did not account for this potential bias, and gene expression studies that did use personalized alignments of HLA genes did not examine sex differences 50,51 . Using unbiased estimates of HLA gene expression levels and genome-wide approaches to identify sex-specific patterns, we made the novel observation of an enrichment of LPS responses exhibiting sex by treatment interactions among class I and II HLA genes compared to all autosomal genes: 47% of HLA genes showed sex by treatment interactions whereas these interactions were observed in 8% of all autosomal genes (P = 1.1 × 10 -4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous epidemiological reports have suggested that the incidence and symptoms of adult asthma are higher and more severe in women than in males ( Chen et al, 2003 ; Zein and Erzurum, 2015 ). A recent study that performed sex-specific transcriptomics in 5 tissues from asthma patients also showed sexual dimorphism in asthma, including sex-specific dysregulation of genes and signaling pathways ( Gautam et al, 2019 ). Moreover, the effect of BMI on asthma is greater in female than male adults ( Chen et al, 2002 ; Guerra et al, 2002 ; Beuther and Sutherland, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The testosterone changes were also associated with the initiation of puberty regulated by the production of NUCB2/nesfatin-1 via adipose tissue and NUCB2 gastric output (33). Another possible explanation for this gender disparity could be that variations in NUCB2 could have sex-specific phenotypic effects in T2DM, as illuminated in several other diseases (34,35). But the The given P value were sex-age-adjusted in the total population, and age-adjusted in female or male subgroup.…”
Section: Discussionmentioning
confidence: 99%